Bad apples or bad leaders? : before they can address workplace deviance, leaders need to recognize the role they may be playing - McAllister, Charn Patrick, 1983-; Mackey, Jeremy D.; Ellen, B. Parker; Alexander, Katherine C. (MIT Sloan Management Review, 2023)
Research shows that the prevailing assumption that workplace deviance stems from a few bad apples is mistaken. Leaders have as strong, if not a stronger, effect on whether employees engage in deviant behaviors than is usually acknowledged. Thus, when employees act badly, savvy leaders take a step back and consider whether and how they may be complicit in that behavior.